Presence and inducibility by β-Naphtoflavone of CYP 1A1, CYP 1B1, UDP-GT, GST and DT-Diaphorase enzymes in Trematomus bernacchii, an Antarctic fish. - DI BELLO D; VACCAIO E; LONGO V; NIGRO M; GERVASI PG; PRETTI C.; REGOLI, Francesco; BENEDETTI, MAURA (Aquatic Toxicology, 2007)
This study investigated some aspects of xenobiotic metabolism in the Nototheniidae Trematomus bernacchii, a key sentinel species for monitoring Antarctic ecosystems. After laboratory exposure to β-naphthoflavone (βNF), basal levels and time-course induction of CYP1A, CYP1B and CYP3A were measured as enzymatic activities, immunoreactive protein content and mRNA expression in liver, gills, intestine and heart. Additional analyses in the liver included enzymatic activities of testosterone hydroxylase, (ω)- and (ω - 1)-lauric acid hydroxylase and some phase II enzymes related to the AhR battery genes, DT-diaphorase, glutathione S-transferases and UDP-glucuronyl transferases. Responsiveness of hepatic CYP1A1 after exposure to βNF demonstrated an higher sensitivity of MEROD than EROD activity and long lasting expression of mRNA still induced after 20 days from the treatment. Testosterone metabolism, oxidation of lauric acid and activities of phase II enzymes were not affected by βNF indicating that their modulation is not mediated by Ah receptor. Induction of CYP1A was more limited in gills and absent in intestine and heart. The first nucleotide sequence for CYP1B1 in an Antarctic fish has been obtained, revealing a homology of 89% and 72% respectively to CYP1B1 of plaice and CYP1B2 of carp. Constitutive expression of CYP1B1 was restricted to gills where it was also induced by βNF. Obtained results represent an additional contribution to the ecotoxicological characterization of T. bernacchii and further support the use of biomarkers for early detection of chemical pollution in Antarctica.